The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1017/gmh.2017.16
|View full text |Cite
|
Sign up to set email alerts
|

Development and cross-cultural testing of the International Depression Symptom Scale (IDSS): a measurement instrument designed to represent global presentations of depression

Abstract: BackgroundSelf-report measurement instruments are commonly used to screen for mental health disorders in Low and Middle-Income Countries (LMIC). The Western origins of most depression instruments may constitute a bias when used globally. Western measures based on the DSM, do not fully capture the expression of depression globally. We developed a self-report scale design to address this limitation, the International Depression Symptom Scale-General version (IDSS-G), based on empirical evidence of the signs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…For example, several items were interpreted in FGDs as non-specific to mental illness, such as tummy aches, not enjoying food, or trouble sleeping. Previous studies have likewise found that such items require specific adaptations to differentiate them from experiences of diarrheal disease, hunger, or other stressors (Kohrt et al ., 2007, 2011, 2016; Hanlon et al ., 2008; Kaiser et al ., 2013; Haroz et al ., 2017; Mazzuca et al ., 2019). While some of these items appeared to function well following adaptation (e.g., not enjoying food), other items (e.g., tummy aches) were endorsed in a different pattern than other items, suggesting that they might continue to be endorsed outside the experience of emotional distress.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several items were interpreted in FGDs as non-specific to mental illness, such as tummy aches, not enjoying food, or trouble sleeping. Previous studies have likewise found that such items require specific adaptations to differentiate them from experiences of diarrheal disease, hunger, or other stressors (Kohrt et al ., 2007, 2011, 2016; Hanlon et al ., 2008; Kaiser et al ., 2013; Haroz et al ., 2017; Mazzuca et al ., 2019). While some of these items appeared to function well following adaptation (e.g., not enjoying food), other items (e.g., tummy aches) were endorsed in a different pattern than other items, suggesting that they might continue to be endorsed outside the experience of emotional distress.…”
Section: Discussionmentioning
confidence: 99%
“…These kinds of measures are frequently lacking for conflict-affected populations, owing to difficulty and cost of local adaptation and testing. The methods and procedures used in this study (and based on research described elsewhere [ 10 , 11 , 13 ]) were designed for relatively rapid investigations among conflict-affected populations.…”
Section: Discussionmentioning
confidence: 99%
“…Lacking locally validated measures, we tried to match the findings of the qualitative study to instruments our team had previously developed for cross-cultural use: the International Depression Symptoms Scale (IDSS) [ 13 ] and the Global Post Traumatic Stress Symptom Scale (GPTSS) [ 14 ]. The IDSS and GPTSS are self-report measures made up of a core set of symptoms—for depression and post-traumatic stress, respectively—that have been found through literature review to occur across diverse populations.…”
Section: Methodsmentioning
confidence: 99%
“…The baseline assessment consists of demographic information and scales to measure our primary outcomes: symptoms of depression, PTS, and impaired functioning; and secondary outcomes: alcohol use and anxiety symptoms. Briefly, based on our initial qualitative work, we identified, adapted, and tested appropriate mental health scales, including the International Depression Symptom Scale (IDSS) [ 34 ], the Global Post-traumatic Stress Symptom Scale (GPTSS) [ 35 ], the Anxiety sub-scale of the Hopkins Symptom Checklist (HSCL-A), and the Alcohol Smoking and Substance Involvement Screening Test (ASSIST 3.0) [ 36 , 37 ]. The IDSS and GPTSS were developed based on presentation of depression and PTS globally.…”
Section: Methodsmentioning
confidence: 99%